Science, for What? Or: Science with Conscience - The Invisible College of Dissenting Nuclear Scientists - Franco Ferrarotti (Academicus, 2019)
The main contention of this essay is that sciences can be seen as belonging to two broad categories: a) demonstrative; b) interpretative. Demonstrative, or «tough», sciences are «natural» sciences; interpretative sciences are philosophy, history, all the social sciences, different as thy are (for instance, history is based on causal imputation; sociology, on conditional comparative approach). At present all sciences cannot presume to offer universally valid «laws», timeless and spaceless, but only general, probabilistic tendencies. Moreover, contrary to a misconception Max Weber’s «Wertfreiheit», no science is neutral. It pertains to the social responsibility of scientists the pratical use of eventual scientific findings (for instance, the atomic or the hydrogen bomb).